The predator-prey model on squids and anchovies fisheries in Jepara District, Central Java, Indonesia - Dian Wijayanto; Azis Bambang; Faik Kurohman (Society for Indonesian Biodiversity, 2020)
Abstract. Wijayanto D, Bambang AN, Kurohman F. 2020. The predator-prey model on squids and anchovies fisheries in Jepara District, Central Java, Indonesia. Biodiversitas 21: 5698-5703. Traditional fisheries dominate marine fisheries in Jepara District, Central Java, Indonesia, including the lift net. The catch of the lift net includes squids and anchovies. The ecological relationship between squids and anchovies must be investigated to develop squids and anchovies management. Without proper modeling, the management of anchovies and squids can lead to over-exploitation of both types of commodities. This study aimed to develop the predator-prey model of squids and anchovies fish in the Jepara District. We conducted predator-prey modeling in squids and anchovies using production and fishing effort data from 2010 to 2019. This research showed a predator-prey relationship between squids (as a predator) and anchovies (as prey) in Jepara District. The anchovy’s production function follows the equation: CA = 14,507 E-51 E2 + 0.41 CS or CA = 4,444 E-15.49 E2. The production function of squids follows the equation: CS = 35,156 E-124 E2-2.42 CA or CS = 24,385 E-86 E2. The optimal fishing effort for anchovies and squids production is 144 units of lift net and 141 units of lift net.